تقييم فعالية المعالجة النبضية بالإيزوتريتينوئين في معالجة العد الشائع - معلا, محمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت دراستنا 120 مريضاً عد شائع متوسط الشدة إلى شديد. خضع المرضى لمعالجة نبضية بالإيزوتريتينوئين بجرعة 0,75 مغ/كغ مرة واحدة أسبوعيا لمدة 24 أسبوعاً. تم تقييم التطورات السريرية والتغيرات المخبرية وكذلك الآثار الجانبية كل أربعة أسابيع أثناء فترة المعالجة. كما تمت متابعة الحالة السريرية للمرضى شهرياً لمدة ثلاثة أشهر بعد انتهاء المعالجة. أظهرت هذه الدراسة نتائج علاجية ممتازة بنسبة %95,83 مع تغيرات مخبرية طفيفة كان أبرزها ارتفاع الشحوم الثلاثية (%8,33) وآثار جانبية قليلة أكثرها شيوعا التهاب الشفة (%18,33). تبين نتائج دراستنا أن المعالجة النبضية بالإيزوتريتينوئين فعالة في معالجة العد اشائع وبآثار جانبية قليلة نسبيا. Our study included 120 patients with moderate to severe acne. The patients were treated with pulse isotretinoin therapy in a dose of 0,75 mg /kg once weekly for 24 weeks .The clinical developments, laboratory changes, and side effects were evaluated up weekly at the period of treatment. The clinical status was followed up monthly for three months after the end of treatment. This study showed excellent treating results with mild laboratory changes, the main of which was elevation of triglycerides (8,33%) ; and few side effects, the main of which was chielitis (18,33%). According to our results, Pulse isotretinoin therapy is effective in acne vulgaris, with relatively mild side effects